2006
DOI: 10.1681/asn.2006020161
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the Renal Cyclic 3′-5′-Guanosine Monophosphate System with Type V Phosphodiesterase Inhibition and Exogenous Natriuretic Peptide

Abstract: Type V phosphodiesterase (PDE V) metabolizes cyclic guanosine monophosphate (cGMP) and is abundant in the kidney and vasculature and was found recently in the heart. Sildenafil is a PDE V inhibitor that is used clinically for erectile dysfunction. Brain natriuretic peptide (BNP) is a cardiac peptide with vasodilating, lusitropic, and natriuretic properties that are mediated via cGMP. It was hypothesized that chronic inhibition of PDE V (PDE VI) will enhance the renal actions of exogenous BNP by potentiating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 21 publications
1
49
0
2
Order By: Relevance
“…These results suggest that survival benefit would depend on the duration of functional cGMP levels in the lungs that can reduce MPAP rather than a maximum level, because the retention time in lungs will correlate with the exposure of tadalafil that is proportionally elevated with the doses, and the longer sustained relaxation of the pulmonary vasculature will reduce RV stress and delay the time to RV failure. In addition, there have been reports that inhibition of PDE5 potentiated the response to natriuretic peptides (NPs) in failing hearts (37,38). NPs such as atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) act protectively on the cardiovascular system through diuresis, vasodilation, and inhibition of the renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that survival benefit would depend on the duration of functional cGMP levels in the lungs that can reduce MPAP rather than a maximum level, because the retention time in lungs will correlate with the exposure of tadalafil that is proportionally elevated with the doses, and the longer sustained relaxation of the pulmonary vasculature will reduce RV stress and delay the time to RV failure. In addition, there have been reports that inhibition of PDE5 potentiated the response to natriuretic peptides (NPs) in failing hearts (37,38). NPs such as atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) act protectively on the cardiovascular system through diuresis, vasodilation, and inhibition of the renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 99%
“…[184][185][186][187][188][189] In one canine study, 188 tolerance was not observed following chronic administration of BNP. Development of orally available peptides has long been a challenge, given various barriers to protein absorption and penetration.…”
Section: Dovepressmentioning
confidence: 99%
“…Supporting studies need to be conducted in humans to define the synergy between phosphodiesterase V inhibition and BNP. 29,30 In summary, the idea that we can take a peptide that is synthesized in the heart and that possesses intrinsic cardiorenal protective and enhancing actions and transform it into an effective drug for the treatment of CHF is exciting. The FUSION II investigators are to be congratulated for providing us with important new knowledge about nesiritide in a large clinical trial that helps point us in new directions.…”
Section: Article Pmentioning
confidence: 99%